Dixit. Gra filozoficzna zamiast gamingu - Mazurkiewicz, Mariusz (ETHICS IN PROGRESS, 2013)
This article presents an alternative way of organizing lessons using games. Dixit is a game that facilitates mental development, including development of imagination, creative and critical thinking, social skills, and of an increased sense of belonging to the group. It makes the student more willing to take part in lessons and positively perceive their school life. In the era of widely available gaming, great variety of interactive games, daily availability of iPads and tablets, students’ interest in the lesson is sometimes more difficult. Especially when it concerns the activities in which the student decides whether he wants to attend. An example would be ethics or philosophy; on these lessons, although voluntary participation, there is a subject no less important than those taught compulsorily. The role of the teacher is to organize lessons for the student, which will encourage participation and facilitate the transfer of knowledge on the topic.